Kelayakan LKS Berdasarkan Keterampilan Proses Sains Pada Materi Cahaya - Mardaya Mardaya; Mai Ratih Kumalasari; Dina Marganingsih (Universitas Hamzanwadi, 2022)
This research aims to determine how to develop and determine the eligibility of student worksheet based on science process skills in the subject aboutlight.This research was conducted using the Research and Development (R&D) method. This research is a development research using the 4D development model, which is limited to 3D, namely define, design, development. The student worksheets consist of six activities arranged based on indicators of basic science process skills. Data collection techniques in this study used expert validation data collection techniques. The result show that the average of total percentage by media expert assessment and material expert assessment is about 67.84%. In the other word, the illegibility indicated that the student worksheet as media is feasible.